a) -4x-3=13
b) 2(x+4)+6x=8
proszę o pomoc :))) ​


Odpowiedź :

Odpowiedź:

a)

-4x - 3 = 13

-4x = 16

x = -4

b)

2(x+4)+6x=8

2x + 8 + 6x = 8

8x = 0

x = 0

Odpowiedź:

a)   -4x -3= 13

    -4x= 13 +3

  -4x= 16 /:4

    x= - 4

spr...   -4 *(-4 ) -3= 13

               16-3 = 13

                13 = 13

                 L=P

b)    2 ( x+4) +6x= 8

         2x +8 +6x= 8

         8x= 8 -8

           8x= 0

            x=0

spr...   2*0 +8 +6*0 =8

                 8=8

                 l=P

Szczegółowe wyjaśnienie: